Investigating the Relationship between Neuro-Linguistic Programming Techniques and EFL Classroom Management Satisfaction - Harrif, Maroua (International Journal of Linguistics and Translation Studies, 2025)
Neuro-Linguistic Programming (NLP) studies very closely the processes people use to build their unique, distinctive maps or models of the world. Bandler (1979) asserts that NLP is an attitude and a methodology, which leaves behind a trail of techniques. This study investigated the relationship between NLP techniques and Classroom Management (CM) Satisfaction. Eight NLP techniques including Win-win Situation, Representational Systems, Chunking, Pacing to lead, Modeling, Maintain Rapport, Anchoring, and Outcome Checklist are examined in this paper in terms of their correlation with CM Satisfaction. The Participants (N = 200) completed a self-administered questionnaire (SAQ) divided into two parts. The first part had to do with CM satisfaction. The second part contained eight questions related to NLP techniques. To achieve the purpose, the researcher has adopted a correlational research design, and the main variables were NLP Techniques and CM Satisfaction. Cronbach Alpha was used to measure the internal consistency between items in the scale, and Pearson’s correlation coefficient to analyze the relationship between CM Satisfaction, the dependent variable, and NLP techniques, the independent variable. The analysis of the results shows that Pearson’s Correlation Coefficients of the variables used in this research paper vary between ⟦r =.556 and r =.886⟧. Therefore, CM Satisfaction and NLP Techniques are correlated positively and all the hypotheses tested are confirmed. It was concluded that there is a positive relationship between CM Satisfaction and NLP Techniques.